2006
DOI: 10.1007/s00216-006-0833-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of antibiotics and an antioxidant on the stability of tissue reference materials for domoic acid, the amnesic shellfish poison

Abstract: Five separate reference materials (RMs) were prepared from a mussel (Mytilus edulis) tissue containing domoic acid (DA) from scallop hepatopancreas (Pecten maximus). Homogenates were separately spiked with antibiotics, an antioxidant, or a combination of both. Control materials did not contain any additives and were prepared from lightly cooked and autoclaved mussel tissues. Stability studies were run over a 148-day period at three different temperature conditions: -20 degrees C, +4 degrees C and +40 degrees C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…With the increased use of LC-MS for multi-toxin monitoring, the need for a CRM certified for multiple groups of toxins has also increased. An international collaboration to produce a freeze-dried mussel tissue (Mytilus edulis) CRM (CRM-FDMT1) [11] was initiated following a series of feasibility studies [7,[11][12][13][14][15]. This Electronic supplementary material The online version of this article (doi:10.1007/s00216-016-0004-0) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…With the increased use of LC-MS for multi-toxin monitoring, the need for a CRM certified for multiple groups of toxins has also increased. An international collaboration to produce a freeze-dried mussel tissue (Mytilus edulis) CRM (CRM-FDMT1) [11] was initiated following a series of feasibility studies [7,[11][12][13][14][15]. This Electronic supplementary material The online version of this article (doi:10.1007/s00216-016-0004-0) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…During this moisture adjustment step, a number of stabilizing agents were added at a concentration of 0.02 % (w/ w) in the final material. Previous studies have shown that a combination of antioxidant and antibiotics is beneficial for the stability of some shellfish toxins, and importantly, they are beneficial for the stability of the mussel matrix [38].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the oxidative rancidity of lamb meat increased with increasing dose of radiation [11] but use of small quantities of antioxidants have been shown to inhibit this lipid peroxidation [12]. Parallel studies have shown that use of antioxidants alone can improve the stability of DA in mussel tissue RMs [13] and they have been used in the preparation of the matrix CRMs available for shellfish toxins [1].…”
Section: Discussionmentioning
confidence: 99%